MAL De Meleda Type Of Keratoderma - Pandhi Deepika; Reddy BSN (Wolters Kluwer Medknow Publications, 2001)
A child born of a consanguineous marriage showing characteristic features of Mal de Meleda type of palmoplantar keratoderma is reported for its rarity and clinical interest.